Perancangan Sistem Pengelolaan Data Persediaan Barang Menggunakan Visual Basic Pada PT.Unibless Indo Multi - Hazbi Santoso; Fachri Zaini; Firman Noor Hasan (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
PT Unibless Indo Multi is engaged in IT Services, IT Trading, and IT Outsourcing. In this paper focuses on IT Trading, which includes the sale and rental of IT hardware, the provision of office equipment, the provision of shelves and archival support equipment and others. The author finds problems that occur specifically in the inventory of goods in processing inventory data still using simple applications, which causes the company's performance to be less than optimal. The author aims to solve existing problems by designing and building an inventory data management system using visual basic with the waterfall method, Unified Modeling Language (UML), Balsamiq Mockup and using a Microsoft Access database. Based on the test results using blackbox testing, the system runs as expected. After testing, 92.5 out of 7 respondents agreed that the system is easy to understand and use.